Antimicrobial Potential of Utricularia stellaris Extracts: A promising natural therapeutics to curb infectious pathogen - Pravin K. Thikare; Vaishali U. Thool; Vasanta I. Kahalkar; Vishnu. G. Jadhav (The Bioscan, 2025)
n managing microbial infections, health departments are facing a slowdown in curbing the antibiotic menace. This concurs with the scenario that in the last decade antibiotic-resistant bacteria are emerging around the globe, necessitating the need to find alternative treatments from natural sources. Carnivorous plants are known for their unique ability to thrive in nutrient-poor environments by capturing and digesting prey. Recent research has focused on their potential as sources of bioactive compounds with antibacterial properties. The present study investigates the antibacterial activity of methanolic, ethanolic, and aqueous extracts of Utricularia stellaris, an aquatic carnivorous plant, against six bacterial strains: Staphylococcus aureus, Enterococcus faecalis, Bacillus subtilis, Escherichia coli, Klebsiella pneumoniae, and Pseudomonas aeruginosa. The result noted that the methanolic extracts exhibited the highest antibacterial activity, particularly against Bacillus subtilis and Staphylococcus aureus, with moderate effects on Escherichia coli, whereas ethanolic extracts showed similar results, demonstrating strong inhibition of gram-positive bacteria, while aqueous extracts displayed limited activity, primarily due to their inability to dissolve non-polar bioactive compounds effectively. Overall, methanolic extract emerged as the most effective solvent across studies, underscoring its superiority in extracting potent bioactive compounds. Notably, Pseudomonas aeruginosa exhibited resistance across all extracts, consistent with its known efflux pump mechanisms and impermeable outer membrane. The findings suggest that Utricularia stellaris is a promising natural source of antibacterial agents, particularly for combating gram-positive pathogens. This study provides a foundation for further research on isolating specific compounds and exploring their potential applications in natural therapeutics.